2015
DOI: 10.1007/s13760-015-0564-3
|View full text |Cite
|
Sign up to set email alerts
|

Restless legs syndrome is associated with poor sleep quality and quality of life in patients with ankylosing spondylitis: a questionnaire-based study

Abstract: We aimed to investigate the frequency of restless legs syndrome (RLS) and the associations between RLS and quality of sleep and life in patients with ankylosing spondylitis (AS). One hundred and eight AS patients and 64 controls were included in this study. Demographics, clinical, and laboratory data were recorded. The presence of RLS was determined with face-to-face interview by an experienced neurologist based on the International RLS Study Group criteria. RLS severity was evaluated using International RLS S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 39 publications
(50 reference statements)
0
17
0
Order By: Relevance
“…Various studies showed the increased frequency of RLS and its association with poor sleep quality in many diseases such as chronic renal failure, [26] fibromyalgia, [27] ankylosing spondylitis, [28] lumbar radiculopathy, [29] inf lammatory bowel disease, [30] or primary biliary cirrhosis. [31] However, there exist only a small number of studies which investigate the relationship between RLS and allergic diseases in adults, but not in children.…”
Section: Discussionmentioning
confidence: 99%
“…Various studies showed the increased frequency of RLS and its association with poor sleep quality in many diseases such as chronic renal failure, [26] fibromyalgia, [27] ankylosing spondylitis, [28] lumbar radiculopathy, [29] inf lammatory bowel disease, [30] or primary biliary cirrhosis. [31] However, there exist only a small number of studies which investigate the relationship between RLS and allergic diseases in adults, but not in children.…”
Section: Discussionmentioning
confidence: 99%
“…Periodic leg movements are seen in 3.9% of the normal population . Demirci et al . used the International Restless Leg Syndrome (RLS) study group criteria to determine the frequency of RLS, which has been known to be associated with PLMI, in patients with AS.…”
Section: Discussionmentioning
confidence: 99%
“…There were no cases considered appropriate from inclusion in the severe (21-30) or very severe (31-40) group. For the controls there was one mild case (0-10) and one moderate case (11)(12)(13)(14)(15)(16)(17)(18)(19)(20).…”
Section: Demographic Data Are Presented In Tablementioning
confidence: 99%
“…RLS patients declare worse global quality of life and important impairments of mental and general physical status compared to healthy individuals or to patients with other conditions (6). There are several diseases/conditions which are suggested to increase the prevalence of RLS: Renal failure (8), kidney transplantation (9), rheumatoid arthritis (10), fibromyalgia (11), lung transplantation (12), migraine (13), ankylosing spondylitis (14) or multiple sclerosis (15). In pregnancy, the prevalence of RLS is also high, but in contrast with the aforementioned conditions, it has a good prognosis, remitting in few weeks/months after delivery (16).…”
Section: Introductionmentioning
confidence: 99%